2020
DOI: 10.1101/2020.04.02.021709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobilization of tissue-resident memory CD4+T lymphocytes and their contribution to a systemic secondary immune reaction

Abstract: While it is generally accepted that tissue-resident memory T lymphocytes protect host tissues from secondary immune challenges, it is unclear whether, and if so, how they contribute to systemic secondary immune responses. Here we show that in human individuals with an established immune memory to measles, mumps and rubella viruses, when challenged with the measles-mumps-rubella (MMR) vaccine again, tissue-resident memory CD4 + T cells are mobilized into the blood within 16 to 48 hours after vaccination. These … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…We hypothesized that antigen-specific stimulation may initiate their mobilization into the blood, allowing further expansion and redistribution into the peripheral tissues for broader spatial coverage of protective immunity, as has been suggested recently in the mouse (21). This phenomenon would be consistent with a recently published study that suggested tight kinetics for T RM cell tissue exit and reentry upon antigen-specific T cell stimulation by vaccination (23).…”
Section: Circulating Memory T Cells Of Host Origin With Tissue Tropis...supporting
confidence: 80%
“…We hypothesized that antigen-specific stimulation may initiate their mobilization into the blood, allowing further expansion and redistribution into the peripheral tissues for broader spatial coverage of protective immunity, as has been suggested recently in the mouse (21). This phenomenon would be consistent with a recently published study that suggested tight kinetics for T RM cell tissue exit and reentry upon antigen-specific T cell stimulation by vaccination (23).…”
Section: Circulating Memory T Cells Of Host Origin With Tissue Tropis...supporting
confidence: 80%
“…It would be intriguing to speculate that there is a functional division of labor between CD69 + and CD69 − memory T cells of the bone marrow in secondary immune reactions: CD69 + memory T cells as bona fide tissue‐(bone marrow‐) resident memory cells remaining in the bone marrow upon reactivation and providing local protection of the hematopoietically so important tissue, and CD69 − memory T cells with the ability to leave the bone marrow and participating in the systemic immune responses and germinal center reactions in secondary lymphoid organs. In recall immune responses an initial wave of antigen‐reactive memory T cells can be observed already 16–48 h after vaccination [103], suggesting direct mobilization into the blood from their tissue of residence (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%